Primary production and Calcite Production from D366, discrete CTD measurements - Poulton, Alex (British Oceanographic Data Centre, Natural Environment Research Council, 2014)
Discrete measurements of calcite production by coccolithophores alongside measurements of primary production measured during the June 2011 UK Ocean Acidification cruise. Measurements collected to examine the distribution and activity of the coccolithophore communities present in shelf seas around the UK.